2010
DOI: 10.1002/chem.200903053
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Open GdIII Metal–Organic Frameworks Based on Methanetriacetic Acid: New Objects with an Old Ligand

Abstract: The preparation, X‐ray crystallography and magnetic investigation of the first examples of methanetriacetate (mta)‐containing lanthanide(III) complexes of formulae [Gd(mta)(H2O)3]n⋅4 n H2O (1) [Gd(mta)(H2O)3]n⋅2 n H2O (2) and [Gd2(mta)2(H2O)2]n⋅2 n H2O (3) are described herein. This tripodal ligand promotes the formation of 63 networks; thus 1 consists of a honeycomb structure, whereas in 2 two of these layers are condensed to form a rare five‐connected two‐dimensional (4862) network. Compound 3 can be seen as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 152 publications
0
9
0
Order By: Relevance
“…The first Eu III -containing methanetriacetate compounds have been synthesized, through gel [for (I)] and hydrothermal methods [for (II) and (III)]. Two of them, (I) and (II), are isomorphous with two Gd III compounds reported previously (Cañ adillas-Delgado et al, 2010), where the main differences arise from the lanthanide contraction. Compound (III) represents a new polymorph.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first Eu III -containing methanetriacetate compounds have been synthesized, through gel [for (I)] and hydrothermal methods [for (II) and (III)]. Two of them, (I) and (II), are isomorphous with two Gd III compounds reported previously (Cañ adillas-Delgado et al, 2010), where the main differences arise from the lanthanide contraction. Compound (III) represents a new polymorph.…”
Section: Discussionmentioning
confidence: 99%
“…Its structure consists of [Eu(H 2 O)] 3+ units and six-connecting mta 3À ligands acting as octahedral and trigonal prismatic nodes, respectively, which result in a three-dimensional network showing the NiAs topology [a (6,6)-connected binodal nia-net (Blatov, 2006), with a (4 12 6 3 )(4 9 6 6 ) Schlä fli symbol], which is quite rare among MOF architectures (Figs. 3 and 4; Delgado-Friedrichs et al, 2006;Chen et al, 2012;Bai et al, 2008;Cañ adillas-Delgado et al, 2010;Chae et al, 2001;Jia et al, 2012). The structure contains chains of oxo-and syn-syn carboxylate-bridged Eu III ions running along the b axis, which are interconnected through the mta 3À ligands to yield the full three-dimensional framework.…”
Section: [Eu(mta)(h 2 O)] N áNh 2 O (Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of the characteristics of organic and inorganic components offers an opportunity to incorporate useful properties within a single composite, providing access to multifunctional materials. Lanthanides attract attention for unique physical properties arising from 4f electrons [6][7][8][9]. High coordination number and flexible coordination geometry of lanthanide ions make it difficult to control preparation of lanthanide compounds.…”
Section: Introductionmentioning
confidence: 99%
“…8 Notably, binodal NiAs-type (nia) topology with both octahedral and trigonal prismatic building blocks is rarely observed in MOFs. [9][10][11][12][13][14] Yaghi et al have reported that a nia-type MOF can be generated by connecting a trigonal prismatic six-node ligand with an octahedral Zn 4 O cluster. 14 Conversely, we think that a nia topology can also be formed by connecting a trigonal prismatic IBB with an octahedral OBB.…”
mentioning
confidence: 99%